ANALYSIS OF STABILITY OF ONE CLASS OF NUMERICAL METHODS OF SECOND ORDER - Zaiats, Vasyl Mykhaylovych (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
The paper deals with the analysis of the stability of a class of second order combined numerical methods based on the trapezoid method and the difference formula, what obtained by the author. The stability conditions for this class of methods are obtained by the example of conservative systems.